Ombudsman's situation in the world - Herrera Damas, Susana (2022)
Although it receives different names, little is known about its activity. It is the ombudsman's role to receive and investigate complaints made by consumers regarding the impartiality and good taste in news coverage. This is the modern sense of the character which dates from 1967 when it was first introduced in an American newspaper. The present article reports on the ombudsman's objectives, its differential characteristics, its functions, its typology, its qualities, its advantages and limitations and clarifies some aspects related to the history of this professional character.